2019
DOI: 10.1002/jbm4.10167
|View full text |Cite
|
Sign up to set email alerts
|

Combination Therapy With Zoledronic Acid and FES‐Row Training Mitigates Bone Loss in Paralyzed Legs: Results of a Randomized Comparative Clinical Trial

Abstract: Spinal cord injury (SCI) results in rapid, severe osteoporosis and an increased risk of lower extremity fractures. Despite the medical complications associated with these fractures, there is no standard of care to prevent osteoporotic fractures following SCI. Functional electrical stimulation‐ (FES‐) assisted rowing is a promising intervention to improve bone health in SCI because of its ability to generate a muscular contraction in conjunction with mechanical loading of the lower extremity long bones. Combina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 39 publications
(77 reference statements)
0
28
0
3
Order By: Relevance
“…Considering the promising role of FES rowing exercise in promoting muscle contraction with combined mechanical loading of lower limb long bones in SCI patients, a therapeutic synergism with drugs acting at the bone level has been proposed (82). This combined strategy could induce both bone resorption inhibition and bone neoformation stimulation.…”
Section: Zoledronic Acid Plus Fes Rowing Exercisementioning
confidence: 99%
See 1 more Smart Citation
“…Considering the promising role of FES rowing exercise in promoting muscle contraction with combined mechanical loading of lower limb long bones in SCI patients, a therapeutic synergism with drugs acting at the bone level has been proposed (82). This combined strategy could induce both bone resorption inhibition and bone neoformation stimulation.…”
Section: Zoledronic Acid Plus Fes Rowing Exercisementioning
confidence: 99%
“…This combined strategy could induce both bone resorption inhibition and bone neoformation stimulation. A randomized clinical trial comparing FES-rowing alone with FES-rowing plus zoledronic acid (a powerful bone anti-resorptive drug), have been carried out to investigate the impact of bone health in SCI (82). The latter group had significantly greater cortical bone volume (CBV) and cortical thickness index (CTI) at both distal femoral and proximal tibial metaphyses, compared to the FES-rowing-only group.…”
Section: Zoledronic Acid Plus Fes Rowing Exercisementioning
confidence: 99%
“…23,24 The role of bisphosphonates administration on increasing bone mass at the knee (distal femur and proximal tibia), the area most susceptible to fractures in patients with SCI/D, is more controversial, with some studies showing no significant benefit 25 and others showing increase in bone mass. 26,27 Teriparatide, which increases osteoblastic activity (thus bone deposition), may have positive effect on increasing bone density of the spine, hip, and knee in individuals with SCI/D-related paralysis, 28 but no studies utilized fracture occurrence as outcomes, thus efficacy in fracture prevention was not assessed.…”
Section: Use Of Dxa In Sci/d-related Paralysismentioning
confidence: 99%
“…Previous studies reported inconsistent bone responses after training with FES-rowing [9][10][11] and a wide range of foot reaction forces generated by SCI rowers (0.22 to 0.67 body weight (BW)) [12][13][14] .…”
Section: Introductionmentioning
confidence: 99%
“…FES-rowing is one exercise intervention that is growing in popularity in SCI rehabilitation 8 . Previous studies reported inconsistent bone responses after training with FES-rowing 911 and a wide range of foot reaction forces generated by SCI rowers (0.22 to 0.67 body weight (BW)) 1214 . These variable results, combined with observations that bone adapts to its mechanical loading environment, suggest that foot loading influences subsequent changes in lower extremity bone in FES-rowing.…”
Section: Introductionmentioning
confidence: 99%